(untitled) (Progressive Agriculture, 2013)
Experiments were conducted to develop and standardize the protocols for cryopreservation of sperm of grass carp (Ctenopharyngodon idella). Seven extenders such as Alsevers solution, Urea egg-yolk, Egg-yolk citrate, Kurokura- 1, Kurokura-2, 0.9% NaCl and 0.6% Glucose and five cryoprotectants i.e. DMSO, methanol, ethanol, DMA and glycerol were employed for finding suitable combinations. Cryodiluents were prepared by mixing the cryoprotectants at 10% concentration of the extenders (v/v). Milt and cryodiluents were mixed at a ratio of 1:9 for Alsevers solution, Kurokura-1, Kurokura-2, 0.9% NaCl and 0.6% glucose, and 1:4 for urea egg-yolk and egg-yolk citrate. Among the 35 combinations of extenders and cryoprotectants, Alsevers solution with ethanol and methanol, urea egg-yolk and egg-yolk citrate with DMSO found suitable for preservation and it produced 74 ± 2.44%, 72 ± 2.54%, 76 ± 2.44% and 75 ± 2.23% spermatozoan motility at the post-thaw period respectively. Rest of the combinations, on the other hand, produced <60% motility at the post-thaw period and glycerol was found to be clotted after freezing. The dilution of milt with cryodiluent has been tested using six dilution ratios (1:2, 1:4, 1:7, 1:9, 1:15, 1:20) and found that 1:9 dilution ratio produced the highest post-thaw spermatozoan motility with Alsevers solution (>75%) and 1:4 with urea eggyolk and egg-yolk citrate (>70%). As an optimum level of cryoprotectant, 10% concentration was found effective to produce significantly highest (P<0.05) percentage of spermatozoan motility compared to those of other four concentrations (5, 15, 20 and 30%). DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16763 Progress. Agric. 21(1 & 2): 141 - 150, 2010